Nasal Amyloidosis in a Horse - Portela, Roseane A.; Dantas, Antônio Flávio M.; Melo, Diego Barreto de; Marinho, Josemar Medeiros; Nóbrega Neto, Pedro Isidro da; Riet-Correa, Franklin (Brazilian Journal of Veterinary Pathology, 2012)
A 16-year-old Quarter Horse was admitted to the Veterinary Hospital after recurrent epistaxis episodes. Dyspnea and intolerance to exercise were noticed. An irregular multinodular mass was observed in the mucosa of the rostral nasal cavity, causing partial stenosis of the anterior airways. To improve the respiratory condition of the animal, most of the mass was surgically removed. Histologic examination revealed eosinophilic hyaline material in the lamina propria, walls of submucosal lymphatic and blood vessels, and basement membrane of mucosal glands of the nasal cavity. This material stained orange-red with Congo-red, with the characteristic green birefringence under polarizing light, confirming the amyloid diagnosis. Giant cells and mononuclear cell infiltrate were also observed. One year after the partial removal of the lesion, the horse had only mild respiratory signs.